Transparansi dan Akuntabilitas Penjualan Barang Milik Negara Ardjuna Sakti dalam Mewujudkan Good Governance - Sitanggang, Friska (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
This research examines the application of the principles of transparency and accountability in the Ardjuna Sakti State Property (BMN) sales process as an effort to realise good governance in Indonesia. This research uses a descriptive qualitative method, with a case study approach through document analysis, regulations and interviews. Data was collected from various relevant stakeholders, especially BMN sales implementers. The results show that Ardjuna Sakti's BMN sales process has followed the established procedures, but there are still some challenges in implementing the principles of transparency and accountability. The role of ASN in ensuring information disclosure and accountability to the public is key in realising good governance. This study concludes that improving transparency and accountability in Ardjuna Sakti's BMN sales is essential to realising good governance. The proposed recommendations include improving information systems, increasing public participation, and strengthening supervisory mechanisms. The implications of this study contribute to a better understanding of state asset management practices and the realisation of good governance in Indonesia.